Watching eyes effect: the impact of imagined eyes on prosocial behavior and satisfactions in the dictator game - Lv, Jieyu; Shen, Yuxin; Huang, Zheng; Zhang, Chujian; Meijiu, Jiangcheng; Zhang, Hongchuan (Frontiers in Psychology, 2024)
The concept of the watching eyes effect suggests that the presence of eye or eye-like cues can influence individual prosocial behaviour. However, few studies have investigated the effects of imagined eyes on prosocial behaviours and the psychological measures of dictators and recipients in the dictator game. This study explored the effects of imagined eyes on individual behaviour and psychological measures in the dictator game, employing a 2 (Presentation Mode: Imagined/Visual) × 2 (Cue Type: Eye/Flower) between-subject design. The results revealed a significant interaction between Presentation Mode and Cue Type. In the Visual conditions, the dictators' altruistic behaviour in the Eye condition was significantly greater than that in the Flower condition, supporting the "watching eyes effect". However, in the Imagined conditions, there was no significant difference in altruistic behaviour between the Eye and Flower conditions. Moreover, it was found that, regardless of being imagined or visual, recipients reported greater satisfaction with the dictators and the allocation outcome.Notably, in the Visual Flower condition, dictators used more egoistic norm words when communicating with the recipient than other conditions. There were no significant differences in the use of daily politeness words and altruistic norm words across the four conditions. In addition,the Imagined Flower condition had least emotion expression words; while the Imagined Eye condition had the most. This study provides novel evidence on the effect of imagined social cues on individual behaviour in the dictator game and is thefirst to explore their impact on recipients' psychological measures and the communication between dictators and recipients. These efforts offer new insights into the psychological and cognitive mechanisms underlying the watching eyes effect.